(untitled) (Al-Aasar, 2025)
Imām Ibn al-Qayyim al-Jawziyyah (d. 751 AH) stands out as one of the most profound jurists in Islamic legal thought, particularly in the fields of fiqh, uṣūl al-fiqh, and maqāṣid al-sharīʿah. A central feature of his legal thought is his nuanced treatment of the Prophetic acts. Ibn al-Qayyim classifies these acts according to the functional roles and capacities in which the Prophet ﷺ acted, thereby offering a principled framework for legal interpretation. According to Ibn al-Qayyim, the Prophetic acts can be broadly divided into four categories: acts performed in the capacity of a Messenger conveying divine legislation; acts carried out as a judge resolving disputes through evidence and ijtihād; acts undertaken as a political leader and head of state in managing collective affairs; and acts arising from human nature and personal habit. The first three categories encompass both legislative (tashrīʿī) and administrative or policy-based (tadbīrī) dimensions. Legislative acts establish permanent legal norms binding upon the Ummah, whereas administrative and political acts remain contingent upon time, place, and public interest, allowing room for juristic discretion and renewal. The fourth category, relating to the Prophet’s human and customary practices, is classified by uṣūlī scholars as sunnah ʿādiyyah. While emulation of these acts is virtuous and reflects love and reverence for the Prophet ﷺ, their omission does not entail sin unless supported by specific evidence indicating legislative intent. By distinguishing between these categories, Ibn al-Qayyim provides a balanced and context-sensitive approach that safeguards the authority of the Sunnah while preventing misapplication of Prophetic precedents. His framework remains highly relevant for contemporary Islamic legal reasoning, particularly in differentiating between immutable divine guidance and adaptable governance-based practices.